2014
DOI: 10.4137/cin.s13882
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Biological Pathways Implicated in Lung Cancer from TCGA Gene Expression Data Using Gene Set Enrichment Analysis

Abstract: Analyzing biological system abnormalities in cancer patients based on measures of biological entities, such as gene expression levels, is an important and challenging problem. This paper applies existing methods, Gene Set Enrichment Analysis and Signaling Pathway Impact Analysis, to pathway abnormality analysis in lung cancer using microarray gene expression data. Gene expression data from studies of Lung Squamous Cell Carcinoma (LUSC) in The Cancer Genome Atlas project, and pathway gene set data from the Kyot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…In the last decades, many studies have focused on the pathways related to cell growth and death in tumor formation. More and more results showed that cell cycle pathway and p53 signaling pathway played a key role in the formation of malignant tumors (9,(13)(14)(15). In this study, the researchers observed that cell cycle pathway (all P value < 0.001, from GSEA results of four independent microarray data) and p53 signaling pathway (all P value < 0.001, from GSEA results of four independent microarray data) were positively regulated in NSCLC.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…In the last decades, many studies have focused on the pathways related to cell growth and death in tumor formation. More and more results showed that cell cycle pathway and p53 signaling pathway played a key role in the formation of malignant tumors (9,(13)(14)(15). In this study, the researchers observed that cell cycle pathway (all P value < 0.001, from GSEA results of four independent microarray data) and p53 signaling pathway (all P value < 0.001, from GSEA results of four independent microarray data) were positively regulated in NSCLC.…”
Section: Discussionmentioning
confidence: 63%
“…Among some frequently used gene set analysis methods, gene set enrichment analysis (GSEA) is the most well-known and widely-used approach (7,8), through which the significant difference in expression of pre-defined gene set between two groups of data can be identified. The pre-defined gene set can be a set of genes in a gene ontology category, in a biological pathway, or can be user-defined (9). Recently, using GSEA method, some biological pathways, such as Ras signaling pathway and Wnt signaling pathway were identified to be significantly regulated in NSCLC (9,10), and explained the biological mechanisms of NSCLC.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The top ranked pathways were the viral carcinogenesis pathway, the p53 signaling pathway, and the PI3K-Akt signaling pathway. [29] Another study investigated the regulatory effect of SOX2 on FOXA1 and found that SOX2 was a negative upstream regulator of FOXA1 . These two genes were observed to be altered in 46.4% of 179 TCGA LUSC samples, and the findings of the study may possess future promise in improving the diagnostic efficiency for LUSCs as SOX2 alterations are common for LUSC.…”
Section: Additional Research Based On Tcga Lung Cancer Data Setsmentioning
confidence: 99%